Preschoolers' dynamic respiratory sinus arrhythmia (RSA) change during a challenging parent‐child interactive task: Relations with preschoolers' socioemotional health. Issue 5 (4th November 2020) - West, Kara B.; Shaffer, Anne; Wickrama, Kandauda. A. S.; Han, Zhuo Rachel; Suveg, Cynthia
Abstract: Respiratory sinus arrhythmia (RSA) is a biomarker of physiological functioning that has been implicated in self‐regulatory processes and shown to relate to children's socioemotional health. RSA is a dynamic process reflecting an individual's response to their environment; thus, temporally sensitive methods are critical to better understanding this self‐regulatory process in different contexts. Prior work has studied young children's RSA change in the context of emotion clips and interactions with a stranger. The present study meaningfully expanded upon this work by examining: (a) preschoolers' dynamic RSA change during a challenging task with their mothers, and (b) factors that may explain variability in children's dynamic RSA change. Preschoolers ( N  = 108; M age  = 3.56 years) and their mothers from diverse backgrounds completed a challenging activity together while children's physiological activity was monitored. Mothers reported on children's positive affect, parent emotional support, and family cohesion and indicators of socioemotional health. Children's positive affect and family cohesion explained variability in children's dynamic RSA change, which concurrently related to better socioemotional health. This study advances research and theory on biological correlates implicated in the development of children's self‐regulation and furthers our understanding of factors that may support children's developing self‐regulation at the physiological level.